2002
DOI: 10.1021/jp013675c
|View full text |Cite
|
Sign up to set email alerts
|

Quenching by Oxygen of the Lowest Singlet and Triplet States of Pyrene and the Efficiency of the Formation of Singlet Oxygen in Liquid Solution under High Pressure

Abstract: Quenching by oxygen of the lowest singlet (S1) and triplet (T1) states of pyrene at pressures up to 400 MPa in liquid solution was investigated. The rate constant of the S1 state, k q S, decreased significantly with increasing pressure, while that of the T1 state, k q T, was nearly independent of pressure at the lower pressure region (<100 MPa) and decreased monotonically with further increase in pressure. The activation volume for k q S, ΔV q S⧧, at 0.1 MPa fell in the range of 12−16 cm3/mol, depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 50 publications
8
46
0
Order By: Relevance
“…The triplet state quantum yield (Φ T ) of compound PBI-6 was determined as 51.3%, using the ground-state bleaching method (see Experimental Section for details). This Φ T value of PBI-6 is similar to those reported for other heavy-atom-free PBI derivatives. , It should be pointed out that this value is not always well approximated by the singlet oxygen quantum yields (Φ Δ ). , …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The triplet state quantum yield (Φ T ) of compound PBI-6 was determined as 51.3%, using the ground-state bleaching method (see Experimental Section for details). This Φ T value of PBI-6 is similar to those reported for other heavy-atom-free PBI derivatives. , It should be pointed out that this value is not always well approximated by the singlet oxygen quantum yields (Φ Δ ). , …”
Section: Resultssupporting
confidence: 83%
“…61,73 It should be pointed out that this value is not always well approximated by the singlet oxygen quantum yields (Φ Δ ). 74,75 PBI-6 was used as a triplet photosensitizer to initiate intermolecular triplet−triplet energy transfer (TTET, Figure 6a−i and Figure S26a−i and Figure S27a−f). 76−79 To this end, we selected B-1 as triplet acceptor, a choice justified by, on the one hand, its low T 1 state energy level (1.06 eV, which is smaller than that of PBI-6, 1.34 eV), and on the other hand, its very red-shifted absorption band compared to PBI-6.…”
Section: Resultsmentioning
confidence: 99%
“…Among various photochromic compounds, pyrene and its derivatives with the four-ring-fused planar electron-enriched skeleton are well-known for their unique optical and photoelectronic properties 38. They have been demonstrated to possess a low energy triplet state as well as significant O 2 -induced enhanced intersystem crossing (EISC), which are favourable to generate ROS, especially singlet oxygen ( 1 O 2 ), through energy transfer 39–41. Several pyrene-based MOFs have been investigated for 1 O 2 generation 37,4244.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these results, it was suggested that O 2 quenching of excited triplets exclusively proceeds via singlet encounter complexes, and that no isc takes place between the complexes of different multiplicity. However, later studies provided clear evidence for k T Q values in excess of 1/9k diff 6,17,[22][23][24][25][26][27][28] and even of 4/9k diff , [29][30][31] thus showing that complexes of singlet, triplet, and quintet multiplicity can significantly contribute to the overall mechanism. Moreover, a large number of studies showed that, for easily oxidizable molecules, rate constants correlate with the ease of oxidation of the sensitizer, which means that O 2 quenching of T 1 states proceeds, at least partially, via exciplexes.…”
Section: Introductionmentioning
confidence: 99%